Spread of the African spotted orchid Oeceoclades maculata in the New World - Wetterer, Sarah K. (Universidad de Costa Rica, 2022)
Oeceoclades maculata (Lindl.) Lindl. (= Eulophia maculata (Lindl.) Rchb.f.) has a broad native range across tropical Africa and Madagascar. Here, we document the spread of O. maculata in the New World, using published records, herbarium specimens, photographs posted online, and our own collections. The earliest known New World record of O. maculata is from Brazil dating to before 1790. Until 1962, O. maculata was known in the New World only from South America. Since then, this species has spread north through Central America into Mexico and across the West Indies to Florida and the Bahamas. It was first found in Florida in 1974, and until 1994 all Florida records of O. maculata were restricted to Miami-Dade County (except one record of greenhouse escapees in Gainesville). Here, we document O. maculata records from the following geographic areas in the New World: 11 South American countries (all except Chile and Uruguay), all 7 Central American countries, Mexico, 22 West Indian island-groups, and Florida. We also document records from 31 counties in peninsular Florida. Oeceoclades maculata has now been recorded in the New World from northeastern Rio Grande do Sul, Brazil (~28.5°S) and Estancia Santa Teresa, Corrientes, Argentina (28.0°S) in the south, to Gainesville (29.7°N) and Palm Coast, Florida (29.6°N) in the north. A report of O. maculata populations in Gainesville dying out after a hard frost suggests that this species may have reached its northern outdoor limit in peninsular Florida. Although its impact on native species in the New World appears to be minor, there are efforts to eradicate O. maculata in some natural areas.